Гены устойчивости растений: молекулярная и генетическая организация, функция и эволюция - Шамрай, С.Н. (Журнал общей биологии, 2003)
Remarkable progress is achieved now in comprehension of mechanisms that determine functioning of genes responsible for plants' phytopathogenic resistance (genes R). Cloning of great number of Monocotyledones and Dicotyledones resistance genes show that most of proteins coded by these genes have conserved amino-acid motives, which show high homology to amino-acid motives of proteins with well-designated function. Com-mon structures for most proteins produced by genes R include nucleotide-blinding site (NBS), leucine-rich re-peat (LRR), site containing homology with the cytoplasmic domains of the Drosophila Toll protein and the mammalian interleukin-1 receptor (TIR), coiled-coil structure (СС), transmembrane domain (ТМ), and serine/threonine proteinkinase domain (PK). They are combined within the basic classes of resistance genes proteins as follows: TIR-NBS-LRR, CC-NBS-LRR, NBS-LRR, PK, ТМ-СС, LRR-ТМ, LRR-TM-PK. The domains of proteins produced by plant resistance genes cause specific recognition of avirulence genes products and activate signaling cascade, which gives rise to resistance reaction. Some classes of plant resistance genes probably have the same evolutionary origin as the genes that control the innate immunity of ancient animals. The evolution of plant R genes proceeds primarily by duplication and equal or unequal meiotic re-combination. The research on genes R functioning besides its theoretical value is a matter of considerable prac-tical interest for construction of plant genotypes resistant against harmful organisms. The progress in compre-hension of mechanisms responsible for specificity of avirulence determinants in phytopathogenic organisms recognition makes possible the creation of artificial resistance genes.
Plant Resistance Genes: Molecular and Genetic Organisation, Function and Evolution
Keywords: plants; resistance genes